2016
DOI: 10.3892/ol.2016.4912
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of miRNA-124 and multiple downstream targets is associated with treatment response in myeloid malignancies

Abstract: Abstract. Epigenetic regulation of microRNA (miRNA) expression has recently been implicated in the pathogenesis of myelodysplastic syndrome (MDS). Particular interest has focused on miRNA-124 expression, which is inhibited in MDS and has recently been demonstrated to be upregulated in response to epigenetic treatment (EGT). Previous studies have determined the in vitro and in vivo expression of miRNA-124 and several molecular targets, including cyclin-dependent kinase (CDK) 4, CDK6 and enhancer of zeste homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Castoro et al reported the methylation status of miR-124-1 and miR-124-3 in MDS patients and suggested that the re-expression of miR-124 was a good marker of response to DAC [ 21 ]. Another recent study also demonstrated that high-risk MDS or AML patients who responded to epigenetic treatment showed significant induction of miR-124 and inhibition of CDK4 and CDK6 expression [ 39 ]. However, the role of miR-124 in cell proliferation and the regulation of its target have not been clearly elucidated in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Castoro et al reported the methylation status of miR-124-1 and miR-124-3 in MDS patients and suggested that the re-expression of miR-124 was a good marker of response to DAC [ 21 ]. Another recent study also demonstrated that high-risk MDS or AML patients who responded to epigenetic treatment showed significant induction of miR-124 and inhibition of CDK4 and CDK6 expression [ 39 ]. However, the role of miR-124 in cell proliferation and the regulation of its target have not been clearly elucidated in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs from patients which responded to the combination EGT for high risk MDS or AML demonstrated in vitro significant induction of miR-124 and inhibition of CDK4 and CDK6 (and a trend to inhibit EZH2) mRNA expression. These findings suggest miRNA-124 is a potential biomarker of early response to EGT in myeloid malignancies and a possible therapeutic target ( 45 ).…”
Section: Mirnas Associated With Good Prognosis Of Aml and Their Potenmentioning
confidence: 97%
“…miR-124 expression is inhibited in myelodysplastic syndrome (MDS) and is upregulated in response to epigenetic treatment (EGT) ( 45 , 102 ). The upregulation of miR-124 expression in response to single-agent EGT with either azacytidine (AZA) or the histone deacetylase inhibitor panobinostat (LBH589) reported in vitro in the HL60 leukemic cell line ( 45 ) resulted in inhibition of CDK4, CDK6 and EZH2 expression. Accordingly, combination with EGT led to a significant and additive inhibitory effect.…”
Section: Mirnas Associated With Good Prognosis Of Aml and Their Potenmentioning
confidence: 99%
“…Histone modification may activate or inhibit miRNA expression. HDAC inhibition upregulates miR-124 accompanied by the inhibition of the expression of downstream targets, such as CDK4, CDK6, and EZH2 ( 56 ). miRNA may also regulate histone modifications.…”
Section: Histone Methylation Modificationmentioning
confidence: 99%